Response Surface Methodology for Optimizing Giant Magneto-Resistive (GMR)-Bobbing Coil Probe for Carbon Steel Pipeline Crack Detection - A Faraj, Moneer; Samsuri, Fahmi; N AbdAlla, Ahmed; Rifai, Damhuji; Ali, Kharud; Al-Douri, Y. (International Journal of Engineering and Technology, 2018)
Inspection of inner wall cracks is critical in the evaluation of carbon steel pipe integrity. In this study, the optimization of Giant magneto-resistive (GMR)-Bobbing coil probe (GMR-BC) based eddy current technique for carbon steel pipeline was proposed. Bobbing coil was used in the magnetization of pipe and the GMR sensor array in the identification of field leakages from the pipe crack. Response surface methodology (RSM) was utilized to optimize the dimension which includes GMR sensors, height of the coil, and lift-off depending on the desirability technique. The efficiency of this approach was by estimating the change in the axial component of leakage flux from axial and hole defects artificially machined on the wall pipe. The results obtained experimentally were in good agreement with the predicted mathematical model using RSM in the prediction of axial and hole defect detection. The result reflected that 6 GMR sensors, 2 mm of lift-off, and 10 mm of coil height were the optimum conditions of GMR-BC probe that detected all the axial and hole defect in 60 mm carbon steel pipe.Â Â Â